Synthesis of Unsymmetrically Substituted Tetraphenylenes through Palladium-Catalyzed C(sp2)–H Activation - Wan, Bin; Zhang, Yanghui (Synthesis, 2021)
An efficient protocol for the palladium-catalyzed cross-coupling reaction of 2-iodobiphenyls with biphenylene has been developed through C–H activation. The reaction provides a simple and efficient method for the synthesis of unsymmetrically substituted tetraphenylenes.
Keywords: palladium catalysis; C–H activation; tetraphenylenes; cross-coupling; unsymmetrical substitution